On the Error Estimate for the Isoparametric Finite Element Method (Journal of Computational Mathematics, 1985)
In this paper, the isoparametric element of 2-degree Lagrange type for second order elliptic P.D.E, with nonhomogeneous Dirichlet boundary value is considered. We prove $\|u-u_h\|_{1,Ω}=O(h^2)$, which is the same as $\|u-u_h\|_{1,Ω_h}=O(h^2)$ where $Ω$ and $Ω_h$ in $R^2$ are the domain of the boundary value problem and isoparametric triangulation domain respectively.